Relationship between physicochemical parameters with the occurrence of vibrio cholerae in estuarine - Diviana Tan, Anak Robert (Universiti Malaysia Sarawak (UNIMAS), 2012)
Vibrio cholerae a family member Vibrionaceae is a well-known agent to cause for clinical symptoms of cholera due to production of cholera toxin (ctx) gene. The main infection of the disease is usually from water which corresponding to the name of the disease, "water-borne" disease. Thus, the aim of this study is to establish the relationship between physicochemical parameters with the occurrence of V. cholerae in estuarine areas where water samples were collected at estuarine of Sg. Sarawak. Parameters studied were temperature, salinity and pH value of the water sample collected. The distribution of the bacterium was quantified by using MPN method while the Omp W gene responsible for the identification of the bacterium was used in the Polymerase Chain Reaction (PCR) analysis for detection of Vibrio cholerea. Occurrence of V. cholerae was found to have relationship with temperature, salinity and pH of water the tested in this study.